(untitled) (Nigerian Journal of Physiological Sciences, 2023)
The African giant rat, AGR (Cricetomys gambianus) is a unique rodent known for its keen sense of smell which has enabled its use in the diagnosis of tuberculosis and demining activities in war torn countries. This keen sense of smell and the ability to navigate tight spaces are skills modulated by the olfactory bulb and cerebellum. While the brain is generally susceptible to environmental pollutants such as heavy metals, vanadium has predilection for these two brain regions. This work was thus designed to investigate the probable neurotoxic effect of vanadium on the neuronal cytoarchitecture of the cerebellum and olfactory bulb in this rodent. To achieve this, twelve adults male AGRs were divided into two groups (vanadium and control groups) and were given intraperitoneal injections of 3mg/kg body weight sodium metavanadate and normal saline respectively for 14 days. After which they were sacrificed, and brains harvested for histological investigations using Nissl and Golgi staining techniques. Results from our experiment revealed Purkinje cell degeneration and pyknosis as revealed by a lower intact-pyknotic cell (I-P) ratio, higher pyknotic Purkinje cell density and poor dendritic arborizations in the molecular layer of the cerebellum in the vanadium treated group. In the olfactory bulb, neuronal loss in the glomerular layer was observed as shrunken glomeruli. These neuronal changes have been linked to deficits in motor function and disruption of odor transduction in the olfactory bulb. This work has further demonstrated the neurotoxic effects of vanadium on the cerebellum and olfactory bulb of the AGR and the likely threat it may pose to the translational potentials of this rodent. We therefore propose the use of this rodent as a suitable model for better understanding vanadium induced olfactory and cerebellar dysfunctions.